An advanced bioinformatics approach for analyzing RNA-seq data reveals sigma H-dependent regulation of competence genes in Listeria monocytogenes. (December 2016) - Liu, Yichang; Orsi, Renato; Boor, Kathryn; Wiedmann, Martin; Guariglia-Oropeza, Veronica
Abstract Background Alternative σ factors are important transcriptional regulators in bacteria. While σB has been shown to control a large regulon and play important roles in stress response and virulence in the pathogenListeria monocytogenes, the function of σH has not yet been well defined inListeria, even though σH controls a large regulon in the closely related non-pathogenicBacillus subtilis . Results Using RNA-seq characterization of aL. monocytogenes strain with deletions of all 4 genes encoding alternative σ factors (ΔBCHL ), which was further modified to overexpresssigH (ΔBCHL::P rha -sigH ), we identified 6 transcription units (TUs) that are transcribed from σH -dependent promoters. Five of these TUs had not been previously identified. Identification of these promoters was facilitated by use of a bio-informatics approach that compared normalized RNA-seq coverage (NRC), between ΔBCHL::P rha -sigH and a ΔBCHL control, using sliding windows of 51 nt along the whole genome rather than comparing NRC calculated only for whole genes. Interestingly, we found that three operons that encode competence genes (comGABCDEFG, comEABC, coiA ) are transcribed from σH -dependent promoters. While these promoters were highly conserved inL. monocytogenes, none of them were found in allListeria spp. andcoiA and its σH -dependent promoter were only found inL. monocytogenes . Conclusions Our data indicate that a number ofL. monocytogenes competence genes are regulated by σH . This σH -dependent regulation of competence related genes is conserved in the pathogenL. monocytogenes, but not in other non-pathogenicListeria strains. Combined with prior data that indicated a role of σH in virulence in a mouse model, this suggests a possible novel role of σH -dependent competence genes inL. monocytogenes virulence. Development and implementation of a sliding window approach to identify differential transcription using RNA-seq data, not only allowed for identification of σH -dependent promoters, but also provides a general approach for sensitive identification of differentially transcribed promoters and genes, particularly for genes that are transcribed from multiple promoter elements only some of which show differential transcription.